2022
DOI: 10.1155/2022/9471720
|View full text |Cite|
|
Sign up to set email alerts
|

3D Real Scene Data Collection of Cultural Relics and Historical Sites Based on Digital Image Processing

Abstract: Traditional digital geometry mainly focuses on local geometric features such as curvature and normal of 3D models. Although the curvature can describe the geometric curvature of the model surface, these local geometric properties cannot describe the global functional structure and associated properties of the 3D model. The purpose of this paper was to study the accurate splicing of cultural relic fragments based on the intrinsic structural features of the 3D model, such as geometry, texture, and function, whos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Wang et al [9] proposed digital cultural relic preservation and digital reproduction technology. Li et al [10] analyzed 3D digital features of cultural relics. Murphy et al [11] applied lasers to model buildings.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [9] proposed digital cultural relic preservation and digital reproduction technology. Li et al [10] analyzed 3D digital features of cultural relics. Murphy et al [11] applied lasers to model buildings.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of 3D data acquisition equipment and technology, the location information on 3D objects and scenes can be collected and transmitted in real time [1][2][3][4]. Since discrete point clouds in 3D space contain depth information and can accurately reproduce real-world scenes, they can be used to record and reconstruct 3D scenes [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%